Impact of maximal strength training on countermovement jump phase characteristics in athletes with cerebral palsy - Fleeton, J. R. M.; Sanders R. H.; Fornusek, C. (Journal of Sports Sciences, 2022)
Analysis of the countermovement jump (CMJ) force-time curve phases provides insight into athlete neuromuscular function and methods by which jump height improves in response to training. A CMJ phase analysis and the dynamic strength index (DSI) have yet to be explored in athletes with cerebral palsy (CP). This study aimed to address this knowledge gap. Eleven state- to international-level athletes with CP completed a pre-post maximal strength training intervention with waitlist control. CMJ was assessed via force plate pre/post baseline and after the 12-week intervention. Following the intervention, CMJ height, takeoff velocity, and concentric phase peak and mean force, impulse and mean acceleration improved significantly (p = 0.006-0.001). No changes were observed in any eccentric braking phase variable (p = 0.79-0.13), while DSI lowered (p = 0.03). In athletes with CP, strength training increased CMJ concentric phase peak and mean force and impulse, increasing velocity and acceleration and therefore jump height. DSI lowered due to moderate and small increases in isometric mid-thigh pull and CMJ peak force, respectively. Unlike in non-disabled athletes, strength training did not alter any eccentric phase variable; therefore, other modalities may be required to further optimize jumping performance in athletes with CP.